Die Kooperation zwischen Zentral- und Geschäftsbanken nach dem Zusammenbruch des Währungssystems von Bretton Woods; The Cooperation between Central and Commercial Banks after the Breakdown of the Bretton Woods Monetary System - Friederike Sattler (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– This article looks at the hitherto little-studied transatlantic cooperation between central and commercial banks after the "Nixon shock" of August 1971 and investigates the specific areas and dimensions of their interactions. Using the example of Deutsche Bank and its board member Alfred Herrhausen, this study shows that in search for a new, rules-based world monetary order the internationally active commercial banks not only engaged in a lively exchange of information and opinions, but also increasingly in market-related interactions with the central banks of Europe, the USA and Japan. Accordingly, in future more attention should be paid to commercial banks as independent actors in monetary policy than has been done so far by research in economic history and economics.
Keywords: N20; F02; F33; E58; G15; G21; 330; Central banks; commercial banks; international monetary cooperation; German-American Industry Talks; International Monetary Conference (IMC); Bank for International Settlements (BIS)